HUBUNGAN KEKUATAN OTOT TANGAN DAN POWER LENGAN DENGAN HASIL FORHAND GROUNDSTROKE PADA ATLET UMUR 14-16 TAHUN PUTRA TENIS PURWODADI TENIS CLUB (PTC) TAHUN 2019 (Indonesian Journal for Physical Education and Sport, 2020)
This study used a test survey method. The research sample was 16 male athletes using total sampling. The research method used a test. The test instruments used were a hand grip dynamometer, throwing a medicinball and a hevit test. The data analysis technique used correlation and multiple regression with 2 independent variables, hand muscle strength (x1), arm power (x2), and the result of a forehand (y) as dependent variable. Data analysis using a significant level of 5% is found: 1) The relationship of hand muscle strength to the results of forehand groundstroke is 53.7%, 2) The relationship between arm power and forehand groundstroke is 78.7%, 3) The relationship between hand muscle strength and arm power with a forehand groundstroke result of 78.7%.The conclusions of the study are 1) There is a relationship between the ability of hand muscle strength, 2) There is a relationship between arm power, 3) There is a relationship between the ability of hand muscle strength and arm power with the results of a forehand groundstroke. Suggestions to tennis trainers are 1) to provide exercises that can increase the hand muscles to hold the grip to be more powerful and accurate, 2) to provide a varied training model so that athletes do not get bored in the training to increase arm strength and power.